The Formation of Methodical Competence of the Prospective Teacher of Science through the Interactive Technologies - Shcherbatykh , Sergey V. (International Journal of Psychosocial Rehabilitation, 2020)
Annotation. The relevance of the research is determined by the need to identify optimal models for professional training of prospective science teachers in organizing educational activities of schoolchildren in accordance with the requirements of the Federal State Education Standard of the Secondary General Education (FSES SGE). In the context of shortage of class time for studying methodological content in B.Ed. degree programs, there is a need for intensification of educational activities through interactive technologies. Research objective: theoretically substantiate, develop and experimentally test an organizational and pedagogical model of methodological competence development of prospective science teachers through interactive technologies. The developed model implements methodological guidelines for systemic and integrated, competence-based, activity- based, and technology-based approaches. The peculiarity of this model is that a planned result can be achieved through management of interactive technologies in educational activities. This management is based on correlating interactive technologies with teaching methods implemented in the system of higher education (lecture classes, practical classes, independent work of students, internship), and also with potential of those technologies in developing components of methodological competence of prospective science teachers (personality-centered, cognitive, technological, activity-based). Research methods: pedagogical experiment, questioning, testing, content analysis of curricula, methods of mathematical statistics (chi-square). Research results: a set of conditions that allows to intensify development of methodological competence of prospective science teachers by means of interactive technologies has been identified. Research significance: materials of the article can be useful to administrative and academic staff of educational institutions of higher education.